Sidonius Apollinaris. The Letter To His Friend Turnus. (introd. article, transl. and comment. E.V. Litovchenko) - Litovchenko, Elena V. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
This research contains the introductory article, translation and commentary on one of the letters of Gallo-Roman nobleman and bishop Sidonius Apollinaris. The author analyzes the situation in the Roman world in the fifth century AD, on the eve of the fall of the Western Roman Empire, focusing on the spiritual component. The author links the changes in the minds of the intellectual elite of the Late Roman society with the strengthening of Christianity. As one of the most important tendency of the Late Antiqity’s considered the senatorial aristocracy striving to take holy orders, and act as a pastor. The wide spread of Christianity throughout the Roman Empire, the decline of the role of the senate, the weakening of the central government in the provinces are dealt as an incentives for the development of the mentioned trend. In the article is also charactered the written heritage of Sidonius Apollinaris, which includes poetry and a collection of letters addressed to his friends, acquaintances and colleagues - priests and bishops. The final part of this work is devoted to a translation of the twenty-fourth letter of the fourth book, addressed to Turnus, an acquaintance of Sidonius and to commentary on the text.